2014
DOI: 10.1021/ol501203q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isatins by I2/TBHP Mediated Oxidation of Indoles

Abstract: An I2/TBHP mediated oxidation of commercially available indoles has been developed, which affords isatins in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Unlike C3‐oxygenation, C2‐oxygenation of N ‐methylindole is quite intriguing. It was previously reported in the literature that TBHP/I 2 reagent system facilitated the C2‐oxygenation of (NMe)‐indoles through 3‐iodo iminium intermediate which eventually yielded isatin as the final product . However, during our investigation with TBHP in the absence of I 2 , the formation of C3‐quaternary indolinone 3a was observed instead of isatin derivative.…”
Section: Resultssupporting
confidence: 52%
“…Unlike C3‐oxygenation, C2‐oxygenation of N ‐methylindole is quite intriguing. It was previously reported in the literature that TBHP/I 2 reagent system facilitated the C2‐oxygenation of (NMe)‐indoles through 3‐iodo iminium intermediate which eventually yielded isatin as the final product . However, during our investigation with TBHP in the absence of I 2 , the formation of C3‐quaternary indolinone 3a was observed instead of isatin derivative.…”
Section: Resultssupporting
confidence: 52%
“…In 2011, Wan and co‐workers reported the synthesis of N ‐methylisatin through a ruthenium‐catalyzed oxidative procedure 15. Recently, Ji et al demonstrated the versatile synthesis of isatins through I 2 / tert ‐butyl hydroperoxide (TBHP)‐mediated direct oxidation of indoles 16. Very recently, Kirsch and co‐workers described the direct conversion of indoles into isatins in the presence of 2‐iodoxybenzoic acid (IBX)–SO 3 K/NaI 17.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when the reaction was performed in presence of H 2 18 O (13 μ L), the 18 O labeling products were obtained ( 3 a ‐ 16 O/ 3 a ‐ 18 O=73:27). The 18 O‐labeled experiment demonstrated that the oxygen atom of product came from TBHP or water in the TBHP aqueous solution and Cu(NO 3 ) 2 ⋅ 3H 2 O (see the Supporting Information) …”
Section: Figurementioning
confidence: 99%
“…The plausible mechanism has been proposed in Scheme on the basis of the control experiments and literature precedence ,. Initially, the reaction of sulfonyl hydrazides with tert ‐butylperoxy ( t ‐BuOO . )…”
Section: Figurementioning
confidence: 99%